Contribution to the study of maturation and spawning problems of the sharpsnout seabream (Puntazzo puntazzo) - Georgiou G.; Stephanou D. (Marine aquaculture finfish species diversification, 1995)
The culture of Puntazzo puntazzo began in Cyprus in 1988. Both its culture and market potential were found to be very promising and was soon adopted by commercial fish farms for rearing. Broodstock, however, often either fail to spawn or their spawning is erratic, giving small quantities of poor quality eggs if water temperature is not favourable. In 1991 at the Meneou Experimental Marine Aquaculture Station spawning started early due to a sudden drop of ambient seawater temperature. When the temperature went up again to normal levels, the females kept hydrating, resulting to loss of about 75 per cent of the female broodstock population. Similar problems appeared at the Meneou Station in 1992, 1993 but also in private commercial hatcheries. The female broodstock of P. puntazzo, a hermaphrodite species with the reproduction characteristics of a sequential spawner, after developing the oocyte, failed to spawn. Induced spawning using HCG and a gonadotropin-releasing hormone, did not give any positive results. Further research on the reproduction of this species is needed.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean (TECAM), 1995/06/14-17, Nicosia (Cyprus)